2012
DOI: 10.1111/j.1532-7795.2012.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and Interracial Best Friendships During Middle School: Links to Social and Emotional Well‐being

Abstract: This study examined patterns of intra‐ and interracial best friendships during middle school and their associations with social and emotional well‐being. We hypothesized that intraracial friendships would be beneficial for racial or ethnic minority youth because such relationships provide protection and solidarity in a discriminatory society. Results revealed that most youth had only intraracial best friends during middle school, but 38% had at least one interracial best friend. Associations between interracia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 153 publications
(165 reference statements)
1
29
0
1
Order By: Relevance
“…Multilevel models with child and classroom covariates showed that older students and European American students increased more in their same-race friendships over the school year than did younger students and African American students. This finding is not surprising given studies indicating majority group members and middle grade students show a stronger homophily bias in friendship choices than minority group members and younger grade students (e.g., Hallinan & Teixeira, 1987b;Howes & Wu, 1990;McGill et al, 2012;Shrum et al, 1988). We can be confident these findings are not spurious as they are present in a rigorous change model that accounts for both child characteristics and the composition, structure, and process of the classroom environment.…”
Section: Demographic Predictors: Race and Agesupporting
confidence: 46%
“…Multilevel models with child and classroom covariates showed that older students and European American students increased more in their same-race friendships over the school year than did younger students and African American students. This finding is not surprising given studies indicating majority group members and middle grade students show a stronger homophily bias in friendship choices than minority group members and younger grade students (e.g., Hallinan & Teixeira, 1987b;Howes & Wu, 1990;McGill et al, 2012;Shrum et al, 1988). We can be confident these findings are not spurious as they are present in a rigorous change model that accounts for both child characteristics and the composition, structure, and process of the classroom environment.…”
Section: Demographic Predictors: Race and Agesupporting
confidence: 46%
“…Among the youth of Asian descent, self‐nomination into an Asian crowd was more likely among monoethnic Asian than multiethnic Asian participants who had more ethnically exclusive friendship networks and more positive feelings about their ethnic group, whereas a substantial proportion of variance in peer‐rated crowd affiliations was accounted for by school differences. Similarly, McGill, Way, and Hughes () documented that Asian American youth with only interracial best friends reported lower emotional well‐being than those with only intraracial best friends.…”
Section: Contexts Pertinent To Asian American Child Developmentmentioning
confidence: 92%
“…Positive consequences of cross-ethnic friendships. Research shows that cross-ethnic friendships influence the development of many social and emotional qualities like solving conflicts (McGill, Way, & Hughes, 2012;Nelson & Aboud, 1985) and positively influences self-esteem and socio-emotional support (Hartup & Stevens, 1997;McGill et al, 2012). Kawabata and Crick (2008) investigated how cross-ethnic friendship contributes to social adjustment.…”
Section: Consequences Of Cross-ethnic Friendshipsmentioning
confidence: 99%